ผลของเมทิลเอทิลคีโตนและไซโคลเฮกซาโนนในน้ำยาประสานท่อที่มีต่อสมบัติด้านการยึดติดของข้อต่อพีวีซีแข็ง - จิตตินันท์ จูฑะกาญจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This research aimed to develop a solvent cement for PVC pipe of lower cost while maintaining adequate joint strength. The substitution of tetrahydrofuran (THF), the commonly used solvent, by methyl ethyl ketone (MEK) and cyclohexanone were investigated as the latter two solvents are cheaper and less hazardous. It was found that, in spite of its comparatively poorer ability to diffuse into PVC substrate, MEK could be used as substitute for THF up to 90 percent due to their similarity in the solubility for PVC resins. The cost could then be lower substantially but the amount of volatile chemicals remained more or less the same as both solvents exhibit high vapor pressure. The introduction of low vapor pressure solvent like cyclohexanone up to 30 percent was found to enhance the joint strength appreciably. This was because less evaporation rate caused by the presence of cyclohexanone led to the prolonged retention time at the joint. However too much cyclohexanone addition could result in an adverse effect dueto its relatively poor diffusion power into PVC substrate. Upon considering cost and resulted joint strength, the optimal composition for solvent cement for PVC pipe was found as follows: 15 wt% PVC resin, 4.9 wt% THF, 44.1 wt% MEK, and 36 wt% cyclohexanone.